Only Surgical Treatment to Be Considered for Adhesive Small Bowel Obstruction: A New Paradigm. (23rd October 2018) - Tabchouri, Nicolas; Dussart, David; Giger-Pabst, Urs; Michot, Nicolas; Marques, Frederic; Khalfallah, Meriem; Bucur, Petru; Barbier, Louise; Kraemer-Bucur, Aurore; Nayeri, Mihane; Thiery, Julien; Bourbao-Tournois, Celine; et al.
Abstract : Background . Adhesive small bowel obstruction (SBO) represents a heavy burden in healthcare systems worldwide and is associated with significant morbidity and mortality. Although conservative treatment alone can lead to SBO resolution in most cases, its optimal duration is still a matter of debate. The aim of this study was to analyze different SBO evolution patterns in order to further determine when to switch to surgical treatment. Study Design . All patients who were admitted for adhesive SBO between 2011 and 2016 were reviewed. Patients who had immediate surgery (IS), a successful medical treatment (SMT), and a failed medical treatment (FMT) were compared in terms of overall morbidity, mortality, and SBO recurrence. Results . Overall 154 patients were identified, including 23 (14.9%) in IS, 27 (17.5%) in FMT, and 104 (67.6%) in SMT groups. In terms of comorbidities, patients were similar in all groups. Overall morbidity rates were highest in IS and FMT groups (30% and 33%, respectively, vs. 4% in the SMT group, p < 0.001 ) whereas mortality rate was highest in the FMT group (22% vs. 0% and 0% in IS and SMT groups, respectively, p < 0.001 ). SBO recurrence rate was highest in the SMT group (22% vs. 4% and 7% in IS and FMT groups, respectively, p = 0.042 ). Conclusion . FMT seems to be associated with similar overall morbidity compared with IS but with increased postoperative mortality. Patient frailty seems to be worsened by prolonged inefficient medical treatment.